Utilization of Used Bulbs as Learning Media Innovations to Improve Visual/Spatial Intelligence in Early Childhood - Tripariyanto, Afiff Yudha; Indrasari, Lolyka Dewi; Rahayuningsih, Sri; Komari, Ana (ASEAN Journal of Empowering Community, 2022)
This Community  Service Implementation Activity aims to introduce to early childhood children in   Kasih Ibu schools the use of Waste / Used Materials that can be used as a medium for learning in class and as a medium for recognizing colors and reading so that children are more interested in participating in learning activities in class. With learning media with the bulbs used by  early childhood  , they are provoked and moved to be more willing to  know about how to  analyze colors and how to read easily. This stage in Devotion is the first one we make observations to the Kasih Ibu school, this observation is used as a reference to find out the actual conditions in the field directly. The second stage is the introduction of learning media that utilizes the media of the former bulb, the third stage is  evaluation and monitoring, and the last stage is the results and conclusion. We hope that after carrying out this community service activity, we can increase the interest in learning in mother-love schools so that children in their learning activities are more active, happy, and able to receive material and explanations well and maximally.